38. Remdesivir Treatment in Patients Hospitalized with COVID-19: A Comparative Analysis of In-Hospital All-Cause Mortality. (4th December 2021) - Mozaffari, Essy; Chandak, Aastha; Zhang, Zhiji; Liang, Shuting; Thrun, Mark; Gottlieb, Robert L; Kuritzkes, Daniel R; Sax, Paul; Wohl, David; Casciano, Roman; Hodgkins, Paul; Haubrich, Richard
Abstract: Background: Remdesivir (RDV) reduced time to recovery and mortality in some subgroups of hospitalized patients in the NIAID ACTT-1 RCT compared to placebo. Comparative effectiveness data in clinical practice are limited. Methods: Using the Premier Healthcare Database, we compared survival for adult non-mechanically ventilated hospitalized COVID-19 patients between Aug-Nov 2020 and treated with RDV within 2 days of hospitalization vs. those who did not receive RDV. Preferential within-hospital propensity score matching with replacement was used. Patients were matched on baseline O2 and 2-month admission period and were excluded if discharged within 3 days of RDV initiation (to exclude anticipated discharges/transfers within 72 hrs consistent with ACTT-1 study). Time to 14- and 28-day mortality was examined separately for patients on high-flow/non-invasive ventilation (NIV), low-flow, and no supplemental O2 using Cox Proportional Hazards models. Results: RDV patients (n=27, 559) were matched to unique non-RDV patients (n=15, 617) (Fig 1 ). The two groups were balanced; median age 66 yrs and 73% white (RDV); 68 yrs and 74% white (non-RDV), and 55% male. At baseline, 21% required high-flow O2, 50% low-flow O2, and 29% no O2, overall. Mortality in RDV patients was 9.6% and 13.8% on days 14 and 28, respectively. For non-RDV patients, mortality was 14.0% and 17.3% on days 14 and 28, respectively. Kaplan-Meier curves for time to mortality are shown in Fig 2 . After adjusting for baseline and clinical covariates, RDV patients on no O2 and low-flow O2 had a significantly lower risk of death within 14 days (no O2, HR: 0.69, 95% CI: 0.57—0.83; low-flow, HR: 0.67, 95% CI: 0.59—0.77) and 28 days (no O2, HR: 0.80, 95% CI: 0.68—0.94; low-flow, HR: 0.76, 95% CI: 0.68—0.86). Additionally, RDV patients on high-flow O2 /NIV had a significantly lower risk of death within 14 days (HR: 0.81, 95% CI: 0.70—0.93); but not at 28 days (Fig 3 ). Fig 1. Study Population Fig 2. Kaplan-Meier curves among matched patients hospitalized for COVID-19, August-November 2020 Fig 3. Cox proportional hazard model* for time to mortality among matched patients hospitalized for COVID-19, August-November 2020 Conclusion: In this large study of patients in clinical care hospitalized with COVID-19, we observed a significant reduction of mortality in RDV vs. non-RDV treated patients in those on no O2 or low-flow O2 . Mortality reduction was also seen in patients on high-flow O2 at day 14, but not day 28. These data support the use of RDV early in the course of COVID-19 in hospitalized patients. Disclosures: Essy Mozaffari, PharmD, MPH, MBA, Gilead Sciences (Employee, Shareholder) Aastha Chandak, PhD, Gilead Sciences (Other Financial or Material Support, Employee of Certara (contracted by Gilead to conduct this study)) Zhiji Zhang, MS, Gilead Sciences (Other Financial or Material Support, Employee of Certara (contracted by Gilead to conduct this study)) Shuting Liang, MPH, Gilead Sciences (Employee) Mark Thrun, MD, Gilead Sciences (Employee, Shareholder) Robert L. Gottlieb, MD, Eli Lilly (Scientific Research Study Investigator, Advisor or Review Panel member)Gilead Sciences (Scientific Research Study Investigator, Advisor or Review Panel member, Other Financial or Material Support, Gift in kind to Baylor Scott and White Research Institute for NCT03383419)GSK (Advisor or Review Panel member)Johnson and Johnson (Scientific Research Study Investigator)Kinevant (Scientific Research Study Investigator)Roche/Genentech (Scientific Research Study Investigator) Daniel R. Kuritzkes, MD, Abpro (Consultant)Atea (Consultant, Scientific Research Study Investigator)Decoy (Consultant)Gilead Sciences (Consultant, Grant/Research Support)GSK (Consultant)Janssen (Consultant)Merck (Consultant, Grant/Research Support)Novartis (Scientific Research Study Investigator)Rigel (Consultant)ViiV (Consultant, Grant/Research Support) Paul Sax, MD, Gilead Sciences (Consultant, Grant/Research Support)Janssen (Consultant)Merck (Consultant, Research Grant or Support)ViiV (Consultant, Research Grant or Support) David Wohl, MD, Gilead Sciences (Consultant, Grant/Research Support, Advisor or Review Panel member)Janssen (Consultant, Advisor or Review Panel member)Merck (Consultant, Grant/Research Support, Advisor or Review Panel member)ViiV (Consultant, Grant/Research Support, Advisor or Review Panel member) Roman Casciano, M.Eng, Gilead Sciences (Other Financial or Material Support, Employee of Certara (contracted by Gilead to conduct this study)) Paul Hodgkins, PhD, MSc, Gilead Sciences (Employee, Shareholder) Richard Haubrich, MD, Gilead Sciences (Employee, Shareholder)